Parental smoking is associated with adolescent loneliness : evidence from 71 low- and middle-income countries - Xie, Jintang; Yang, Hui; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers Media S.A., 2025)
Introduction: The association between parental smoking and adolescent mental health is not well understood. We aimed to examine the association between parental smoking and adolescent loneliness using global data collected from the Global School-based Student Health Survey (GSHS) between 2009 and 2019.
Methods: A total of 187,552 adolescents aged 12–15 years in 71 low- and middle-income countries (LMIC) from the GSHS with cross-sectional design were included in this study. Loneliness was defined as feeling lonely sometimes or more frequently in the past 12 months. Parental smoking, reported by the adolescent, was defined as the use of any form of tobacco by the father and/or mother. Logistic regression models were used to examine the odds ratio (OR) of adolescent loneliness according to parental smoking status.
Results: Compared with neither parent smoking, parental smoking was associated with adolescent loneliness (father only: OR = 1.18, 95% CI = 1.10–1.26; mother only: OR = 1.39, 95% CI = 1.15–1.67; both: OR = 1.65, 95% CI = 1.41–1.93) after adjustment for potential covariates. Subgroup analyses stratified by sex, age, and WHO region showed similar results (except not in the African and Western Pacific regions).
Discussion: Parental smoking is associated with loneliness in adolescents from LMIC. Our finding expands the well-known physical damage of parental smoking in adolescents to the psychological damage. Strict policies and strategies should be established to encourage smoking cessation for parents who are current smokers.